"Sincerely Yours, Vera Lynn:" Performing Class, Sentiment, and Femininity in the "People's War" - Baade, Christina (Atlantis)

(untitled) (Mount Saint Vincent University, 2006)
Vera Lynn embodies nostalgic constructions of World War II as a good war. Though phenomenally popular, her radio performances inspired debates over sentimentality and women's voices on air. This article examines how her performances enacted national wartime values while provoking controversy and argues that even "compliant" cultural production does important political work.